FORMATION OF INTELLECTUAL CAPABILITIES OF PRESCHOOL CHILDREN BY INTRODUCING THEM TO SCIENCE AND NATURE - Abdiyeva F.F.; Abdumutallibova N.A. (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Аnnоtаtion: Man is a product of nature. Man was created by nature, perfected. So it is. it is necessary that we honor nature, treat it with the right attitude and contribute to the even more splendor, eternity of nature.